Analysis of Solid and Ionic Surface Reaction Form to Surface Quality when Using Chemical-Mechanical Slurry Polishing - Le Anh Duc; Pham Minh Hieu; Nguyen Trong Mai; Thai Van Trong; Nguyen Minh Quang (Journal of Machine Engineering)
The process of removing machining residues using chemical-mechanical slurry (CMS) has an important place in the creation of ultra-precise components in optical devices. Based on this feature, this work investigates the efficiency of the CMS polishing process by comparing the surface reaction modes by the ionic and solid reaction modes when polishing the yttrium aluminum garnet and sapphire crystal. The study procedures were conducted to clarify the polishing performance corresponding to these two reaction types. The obtained experiments results show that the balance between the mechanical effect process using CMS polishing technology with chemical effect can be achieved with the ionic reaction mode. The results also show that the ionic surface reaction modes give more uniform material removal than the solid reaction on YAG and sapphire crystal surfaces. Therefore, the surface quality when polished by CMS technology with ionic surface reaction modes is better than that of solid surface reaction.